2021
DOI: 10.3389/fneur.2021.666056
|View full text |Cite
|
Sign up to set email alerts
|

Post-Surgical Outcome and Its Determining Factors in Patients Operated on With Focal Cortical Dysplasia Type II—A Retrospective Monocenter Study

Abstract: Purpose: Focal cortical dysplasias (FCDs) are a frequent cause of drug-resistant focal epilepsies. These lesions are in many cases amenable to epilepsy surgery. We examined 12-month and long-term post-surgical outcomes and its predictors including positive family history of epilepsy.Methods: Twelve-month and long-term outcomes regarding seizure control after epilepsy surgery in patients operated on with FCD type II between 2002 and 2019 in the Epilepsy Center of Bonn were evaluated based on patient records and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
(92 reference statements)
1
21
0
Order By: Relevance
“…Epilepsy surgery is a potentially curative option for children with FCD-related epilepsy and can lessen the morbidity and mortality associated with PRE. Our cohort (and others 5,19,27,28 ) exhibits a high seizure-free outcome (Engel I, 72%) with a duration of follow-up of 43.8 months. These data suggest an operational redefinition of pharmacoresistance in the FCD-related epilepsy population, for surgical decision-making, as failure of 1 antiseizure medication and, in turn, advocate for earlier consideration of potentially curative surgery.…”
Section: Discussionmentioning
confidence: 49%
“…Epilepsy surgery is a potentially curative option for children with FCD-related epilepsy and can lessen the morbidity and mortality associated with PRE. Our cohort (and others 5,19,27,28 ) exhibits a high seizure-free outcome (Engel I, 72%) with a duration of follow-up of 43.8 months. These data suggest an operational redefinition of pharmacoresistance in the FCD-related epilepsy population, for surgical decision-making, as failure of 1 antiseizure medication and, in turn, advocate for earlier consideration of potentially curative surgery.…”
Section: Discussionmentioning
confidence: 49%
“…Several studies have shown relationships between pathologic classification and operative results undergoing MRI or PET examination with FCD [ 7 , 15 , 16 ]. However, the relationship between operative results in FCD undergoing MRI and Simultaneous Hybrid PET/MRI examination has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…For the demographic characteristics of patients with Simultaneous Hybrid PET/MRI images, cases with (18F)-FDG PET/MRI positivity had earlier seizure age, surgical age, and disease course, but there were no significant differences ( Table 3 ). However, one study showed that PET/MRI images were more likely to show focal epileptic foci in neonates and infants than MRI images [ 15 ]. Even more study is needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similar results have been reported by numerous other studies. [35][36][37][38][39][40][41][42][43][44] Resection completeness has been judged mostly on an imaging basis, but it has been also assessed by means of invasive EEG 45 or histologic examination of specimen margins. 46…”
Section: Complications Of Surgical Resectionmentioning
confidence: 99%